Virtual Classroom Implementation and Students’ Learning Autonomy in Madrasah Based Digital Learning - Muhalli; Faiqul Imam (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
The accelerated transition from conventional face to face to digital learning models has reshaped instructional paradigms globally, requiring schools to develop both technological infrastructure and learning approaches that support students’ autonomous learning capacities. This study examined the implementation of Virtual Classroom (VC) policy and its implications for students’ learning autonomy at Madrasah Aliyah Negeri (MAN) Bondowoso, an Islamic senior secondary school in East Java, Indonesia. A qualitative descriptive case study design was employed with ten purposively selected informants comprising the principal, vice-principal for curriculum, four teachers, three students from Grades XI–XII, and an IT support staff member. Data were collected through the simak libat cakap method (engaged observation of speech and action), supplemented by in-depth semi structured interviews, non-participant observation, and document analysis. The Miles, Huberman, Saldaña interactive thematic analysis model was applied. Trustworthiness was established through source and technique triangulation, member checking, and audit trail documentation. Four interconnected components of VC implementation were identified: (1) a four-pillar implementation strategy comprising digital infrastructure provision, teacher training, continuous mentoring, and programme integration with national Ministry of Religious Affairs digitalization initiatives; (2) a multi-actor role allocation distributing responsibilities across teachers, students, school management, and IT support staff; (3) bidirectional impacts on learning autonomy positive effects on time management, resource access, digital literacy, and academic performance, alongside negative effects on physical reading and writing literacy; and (4) four challenge categories student technical capacity, student self-regulation, teacher adoption, and infrastructure addressed through targeted institutional mitigation strategies. The findings contribute to the literature on madrasah digital transformation by providing an empirically grounded operational model that integrates institutional, pedagogical, and individual dimensions of VC-mediated learning autonomy in Islamic secondary education.